2017
DOI: 10.1016/j.ecss.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of river floods, hurricanes, and cold fronts to elevation change in a deltaic floodplain, northern Gulf of Mexico, USA

Abstract: Deltas are globally important locations of diverse ecosystems, human settlement and economic activity that are threatened by reductions in sediment delivery, accelerated sea level rise, and subsidence. Here we investigated the relative contribution of river flooding, hurricanes and cold fronts on elevation change in the prograding Wax Lake Delta (WLD). Sediment surface elevation was measured across 87 plots, eight times from February 2008 to August 2011. The high peak discharge river floods in 2008 and 2011 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 60 publications
1
40
0
Order By: Relevance
“…WLD comprises a network of distributary channels and inundated interdistributary deposits flanked by subaerially exposed levees; these zones are commonly referred to as deltaic islands (e.g., Edmonds et al, ; Fagherazzi et al, ; Passalacqua, ). The WLD islands are freshwater wetlands (Howes et al, ) populated by vegetation species that exhibit zonation along the elevation gradient (Bevington et al, ; Carle et al, ). The WLD islands show significant connectivity with the distributary channels and up to 54% of the distributary channel discharge is delivered to the islands before reaching the delta front (Hiatt & Passalacqua, ; Shaw et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…WLD comprises a network of distributary channels and inundated interdistributary deposits flanked by subaerially exposed levees; these zones are commonly referred to as deltaic islands (e.g., Edmonds et al, ; Fagherazzi et al, ; Passalacqua, ). The WLD islands are freshwater wetlands (Howes et al, ) populated by vegetation species that exhibit zonation along the elevation gradient (Bevington et al, ; Carle et al, ). The WLD islands show significant connectivity with the distributary channels and up to 54% of the distributary channel discharge is delivered to the islands before reaching the delta front (Hiatt & Passalacqua, ; Shaw et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…They conclude that high flows, particularly those with high suspended sand concentration, are responsible for deltaic growth. Similarly, Bevington et al, 2017 concluded that increased sediment delivery during floods is associated with subaerial delta accretion in their study on the effect of seasonal forcings (floods, hurricanes, winter cold front passages). They found that the greatest contribution to net elevation gain was from floods, especially those with lower peak discharge but longer duration.…”
Section: Introductionmentioning
confidence: 97%
“…Hence, this field study will be the first to document the effect a flood has on changing subaqueous delta bathymetry over the entire delta front. Floods have been shown to be positively correlated with subaerial delta growth (Bevington, Twilley, Sasser, & Holm, 2017;Carle, Sasser, & Roberts, 2013;Roberts et al, 1980;Rosen & Xu, 2013). Roberts et al, 1980 attributes the sudden emergence and growth of the subaerial portion of the WLD and Atchafalaya Delta to a flood between 1973 and 1975 and argue that subaerial and subaqueous accretion is closely related to the flood cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Areal land growth rates in the WLD range between 1-3 km 2 /year [37]. As this artificial outlet has been allowed to build land under natural hydrologic conditions, the WLD presents an ideal case study for potential river diversion projects aimed at alleviating wetland subsidence and degradation across Louisiana's coast [33].…”
Section: Methodsmentioning
confidence: 99%
“…This study examines the contribution of each remote sensing variable to both herbaceous and forested wetland AGB. Louisiana's Wax Lake Delta offers a valuable case study to estimate coastal wetland biomass estimation, as it is a prograding delta located within the greater Mississippi Deltaic Plain (MDP) where wetlands are severely degrading and receding [32,33] (Figure 1). Coastal Louisiana lost an estimated 4833 km 2 of marsh area from 1932 to 2016, accounting for roughly 25% of its coastal wetlands [34].…”
Section: Introductionmentioning
confidence: 99%